Profit Shifting and Equilibrium Principles of International Taxation - Manon Francois (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the choice between source-based and destination-based corporate taxes in a two-country model, allowing multinational firms to use transfer pricing to allocate profits across tax jurisdictions. We show that source-based taxation is a Nash equilibrium for tax revenue maximizing jurisdictions if domestic and foreign firms generate large revenues. We also show that destination-based taxes are a Nash equilibrium when firms generate low revenues, which implies the presence of multiple equilibria. Both the source and the destination principle coexist in equilibrium when domestic and foreign corporate revenues are intermediate. However, the source principle always tax-dominates the destination principle.
Keywords: F23; H00; H25; H26; H71; 330; tax competition; multinational firms; corporate taxes; transfer pricing